Improving Descriptive Text The Person Writing Skills Through Magic Card in Class VII B Students of SMP Negeri 36 Semarang - Anjani, Ranti Sabilla (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This classroom action research aims to improve students’ ability to write descriptive text through the Magic Card learning model. The subjects in this research were 33 students in class VII B of SMP Negeri 36 Semarang. Data is collected in one cycle through tests, classroom observations, and documentation. The tests were carried out in the form of pre-test, post-test cycle I, and post-test cycle II. The instruments used are test sheets, observation guidelines, and documentation guidelines. Data were analyzed using qualitative descriptive methods. The results show that students take an active role in their learning activities. The quality of their writing also improves. Their average scores increased from 66 (Pre-test), 75 (Cycle I), and 81 (Cycle II). In conclusion, the use of the Magic Card learning model is effective in improving students’ ability to write descriptive text. Researchers hope that the use of the Magic Card learning media can be used by English teachers in teaching English, especially in teaching writing descriptive text